PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI QUICK ON THE DRAW UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMA NEGERI 2 KUANTAN HILIR TAHUN AJARAN 2011/2012 - Rosmaini S; Mariani Natalina L; Riska Elvandari (Biogenesis, 2012)
This study aimed to enhance scientific attitudes and biology student learning outcomes Senior High School Class XI IPA 2 Kuantan Lower School Year 2011/2012 through the implementation of Cooperative Learning Model with the Quick on The Draw Strategy. This research is a class action that was undertaken in January-March 2012. Research subject is a class XI student of SMAN 2 Kuantan Downstream IPA totaling 21 people consisting of 4 students and 17 students. The parameters in this study is a scientific attitude, learning outcomes, and teacher activities. The research instrument consisted of the study and data collection instruments. The procedure consisted of the planning stage, the stage of the exercise of, the stage of observation and reflection stages. Techniques of data analysis consisted of a scientific attitude of students and student learning outcomes. Average of the scientific attitude in the cycle I is 71.73% (enough) is increased in the second cycle with an average of 86.41% which is the scientific attitude (very good). The average student absorption cycle is 65.52% I (quite) and increased in the second cycle with an average 84.81% (good). Thoroughness of student learning in the cycle I is 57.14% (complete) and 42.86% (not complete), and the second cycle increased to 100% (complete) and 0% (not complete). I cycle a group award for all the groups get great rewards. In the second cycle of all the super honored. I cycle activity with the teacher on an average is 95.56% (very good) in the second cycle increased to 100% (very good). From the research concluded with the application of models of cooperative learning strategies Quick On The Draw can improve the attitude of biological science and learning outcomes of students in Class XI IPA SMA Negeri 2 Kuantan Lower School Year 2011/2012.Keywords: Cooperative Model, Learning Outcomes, Quick On The Draw Strategy, Scientific Attitude.